Never give up : an experienced teacher overcomes obstacles to change - Schwille, Sharon A. (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
Never Give Up is an amazing true story. It is a case study of an experienced elementary school teacher who was motivated to change her teaching practices from teacher-centered, transmission approaches to student-centered, transformational approaches in the context of a Professional Development School. You would think she would have accomplished her goal with support from the PDS participants in a year or two. Instead, she spent seven years encountering struggles, set-backs, and occasionally small triumphs until she achieved bone deep change in her teaching practices. What was she aiming for and why did it take so long? How did she finally achieve her goals? This book is about her journey of change.On one level, this is a story of a teacher as she struggles to change her teaching practice in ways that center on children's learning rather than on teacher centered rote learning. On a deeper level, it is a look at how innovative reform movements and wellmeaning professional development efforts fall short of bringing about deep seated change in teaching methods. It raises weighty questions such as how teacher preparation programs should begin the process of instilling habits of exploration, experimentation, research and learning in their pre-service teachers so that they continuously work at updating and upgrading their teaching practices. It is a message to curriculum developers, policy makers and the public at large that lasting teacher professional development takes more time and support than the more immediate workshop approaches. It raises many questions about how teachers learn and how they can keep their practices fresh and innovative throughout their careers.A study guide designed to elicit deep thought and discussion of the many issues raised by this story accompanies the book. The book and study guide are a valuable supplemental text for courses addressing teacher learning, professional development, workplace learning, teacher change, constructivist teaching practices, mentoring, educational administration and educational policy. The study guide is also a tool to stimulate discussion among groups of readers such as pre-service and practicing teachers, school and district administrators, educational policy makers and the public at large who are interested in educational reform.